ASSOCIATION BETWEEN PSYCHOLOGICAL DISTRESS, SLEEP QUALITY, AND VARIABILITY OF PHYSIOLOGICAL VAGINAL DISCHARGE AMONG ADOLESCENT GIRLS - Regina Ayu Fristiyanti; Suci Fitriana Pramudya Wardani; Irna Olvaliani Aimang; Nur Sophia Matin (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Physiological vaginal discharge is a normal condition in adolescent girls, yet variations in its characteristics often cause concern. Psychological distress and sleep quality are suspected to influence the variability of physiological vaginal discharge. This study aimed to analyze the relationship between psychological distress, sleep quality, and the variability of physiological vaginal discharge in adolescent girls. This cross-sectional study involved 120 female students aged 15–18 years at a Banyuwangi Regency high school. Psychological distress was measured using the Kessler Psychological Distress Scale (K10), sleep quality using the Pittsburgh Sleep Quality Index (PSQI), and discharge variability was categorized into "low" and "high" based on secretion characteristics recorded via four-day self-logs. Data analysis employed the chi-square test and logistic regression. Results showed significant associations between psychological distress (p=0.018) and sleep quality (p=0.038) with the variability of physiological vaginal discharge. High psychological distress (OR=4.20; 95% CI: 1.45–12.15; p=0.008), very high psychological distress (OR=6.40; 95% CI: 1.85–22.10; p=0.003), and poor sleep quality (OR=2.75; 95% CI: 1.20–6.30; p=0.017) increased the likelihood of high variability. Psychological distress was the most dominant factor. These findings indicate that psychological aspects and sleep quality can influence the reproductive health of adolescent girls.